Harmony of needs a theory of human motivation and artificial intelligence shaping a new path for Indonesian Education - Anggara, Puput Tri; Dwiningrum, Siti Irene Astuti (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Motivation is the main driver of learning success. Based on A Theory of Human Motivation proposed by Abraham Maslow, motivation grows gradually when basic human needs such as feeling safe, valued, and self-actualization are met. In the context of Indonesian education, which is currently transforming, harmony between fulfilling students' basic needs and technological innovation is an important key to creating a healthy and meaningful learning climate. This article examines how Maslow's principles can be applied in the school environment to increase motivation and build student resilience, namely, their ability to recover from difficulties and remain enthusiastic about learning. In the digital era, artificial intelligence (AI) is opening new paths in education by providing adaptive learning that is able to recognize individual learning needs personally and contextually. AI not only makes the learning process easier but also strengthens the human aspect of education: building empathy, self-confidence, and resilience in students. Although Maslow's theory has drawn criticism, his basic thinking remains relevant as a foundation for forming education that is more responsive, fair, and in favour of the needs of the whole person.